Odbudowa samorządu terytorialnego w Kutnie. Kampania i wybory do rady miejskiej w 1990 r. - Kacprzyk, Ewa (Acta Universitatis Lodziensis. Folia Historica, 2014)
Reconstruction of local authority can be called a process as the first stage were proceedings of Round Table. One of the decisions of the proceedings of Round Table was partially independent parliament election, which took place on 4th of June 1989. However, the first fully democratic election were local authority election on 27th of May 1990. This article presents the course of electoral campaign and election in the small town in the center of Poland – Kutno. The candidates and future representatives of authority in town were presented in statistical way. There were seven committees which participated in that election in Kutno. Moreover, there were 117 people taking part in the election whereas there were 32 mandates and the frequency was 38,76%. Civilian Committee was the one who won the election, there were 24 men and 8 women chosen to be representatives. The City Council of the first term of office had to deal with local problems which mainly derived from structural transformation. That election was the first which presented the social dissatisfaction about horrible economic situation in the country.